2004
DOI: 10.1021/ja0315199
|View full text |Cite
|
Sign up to set email alerts
|

Catalysis with TiO2/Gold Nanocomposites. Effect of Metal Particle Size on the Fermi Level Equilibration

Abstract: Photoexcited semiconductor nanoparticles undergo charge equilibration when they are in contact with metal nanoparticles. Such a charge distribution has direct influence in dictating the energetics of the composite by shifting the Fermi level to more negative potentials. The transfer of electrons to Au nanoparticles has now been probed by exciting TiO(2) nanoparticles under steady-state and laser pulse excitation. Equilibration with the C(60)/C(60)(-) redox couple provides a means to determine the apparent Ferm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

58
1,468
3
12

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,996 publications
(1,541 citation statements)
references
References 64 publications
58
1,468
3
12
Order By: Relevance
“…In contrast to the works of Mohapatra et al, no sulfate species were found in samples prepared by Hidalgo et al, suggesting that different mechanisms would be operative in different reaction conditions [87,88]. The transient absorption decay measurement of Au/TiO 2 at = 675 nm under UV pulse illumination ( = 308 nm) showed less intense signal compared to pure TiO 2 , which was interpreted as indication of accumulation of high number of CB electrons in the Au nanoparticles [89]. In another study it was reported that the visible light induced oxidation of 2-propanol on Au/TiO 2 was initiated by SPR effect as confirmed by action spectrum analysis and they speculated that electron from Au nano particles may be injected into the TiO 2 CB and they in turn reduce the molecular oxygen adsorbed on the TiO 2 surface [90].…”
Section: Photocatalytic Activity Of Gold Deposited Titania (Au/tio 2 )mentioning
confidence: 60%
“…In contrast to the works of Mohapatra et al, no sulfate species were found in samples prepared by Hidalgo et al, suggesting that different mechanisms would be operative in different reaction conditions [87,88]. The transient absorption decay measurement of Au/TiO 2 at = 675 nm under UV pulse illumination ( = 308 nm) showed less intense signal compared to pure TiO 2 , which was interpreted as indication of accumulation of high number of CB electrons in the Au nanoparticles [89]. In another study it was reported that the visible light induced oxidation of 2-propanol on Au/TiO 2 was initiated by SPR effect as confirmed by action spectrum analysis and they speculated that electron from Au nano particles may be injected into the TiO 2 CB and they in turn reduce the molecular oxygen adsorbed on the TiO 2 surface [90].…”
Section: Photocatalytic Activity Of Gold Deposited Titania (Au/tio 2 )mentioning
confidence: 60%
“…10. Although the possible advantages of usage of nanosized gold caused by: decreased the energetic difference between the d-band threshold and the Fermi edge; 41 higher shift in the apparent Fermi level of the TiO 2 -Au composites to more negative potential 42 occurence of a metal-to-nonmetal transition 40b thus gold particles are expected to be semiconducting rather than metallic and a mechanism, based on semiconductorsemiconductor contact (in which photoexcited electrons are injected from gold into the titania CB creating separated electrons and holes which then undergo charge transfer reactions with adsorbates) can be considered; 43 Schottky junction formation (leading to Au-to-TiO 2 electron transfer) 43,44 are well known, our results show that titania modified with gold nanoparticles resulted in much higher  app than did titania modified with nanosized gold. It should be noted that  app is composed of two self-contained parts, i.e., efficiency of absorption and efficiency of electron-hole utilization.…”
Section: Mechanistic Studiesmentioning
confidence: 99%
“…TiO 2 -Ag has attracted particular attention for its non-toxic nature [30], catalytic activity [31,32] and shape-dependent optical properties under visible light [33,34]. Moreover the material could also achieve enhanced photocatalytic efficiency [35]. Thus, a facile and reproducible synthetic route to TiO 2 -Ag and Al 2 O 3 -Ag composite nanoparticles would be useful in a diverse range of applications.…”
Section: Introductionmentioning
confidence: 99%